The Impact of Social Media Marketing on Brand Community Membership: A Higher Education Perspective of University Students’ Experiences in Kuwait - Doha Saleh Almutawaa; Alper Erturk; Vladimir Simovic; Fatima AlLougman; Hamad AlWazzan (Proceedings, 2023)
Consumer identification with brands has received extensive attention in the fields of consumer behavior and psychology. Such consumer-brand identification is conceptualized through the term “brand community”. A brand community is formed when a group of consumers express their interest towards and communicate their identities through a specific brand. The current literature shows that existing research on brand communities appears to be dominantly oriented towards tangible products. Accordingly, this research aims to explore the impact of social media marketing on brand community membership related to an intangible aspect of the self. Contextually, the research seeks to examine the impact of social media marketing of higher education institutions in Kuwait on students’ relevant associations. Students are at the core of higher education institutions due to identifying as both consumers and creators of value. A mixed method approach to data collection and analysis will be employed in this research. The findings of this research are expected to provide important implications for theory and practice.